RESEARCH ON MECHANICAL OF GRAPHENE REINFORCED TIAL SELF-LUBRICATING COMPOSITE MATERIALS - LI WenWen; YANG LiYing; WANG ShouRen; WANG Che (Jixie qiangdu)
Using the method of ultrasonic dispersion and the mechanical ball grinding the graphene mixing in titanium aluminum substrate, pressed by cold pressing molding and vacuum hot-pressing sintering technology of titanium aluminium alloy self-lubricating composites reinforced preparation of graphene. Using scanning electron microscopy（SEM）and transmission electron microscopy（TEM） and energy spectrum analysis（EDS）on microstructure and mechanical properties of the self-lubricating composites were studied. The results showed that graphene in the uniform distribution of titanium alloy substrate and graphene not interface reaction of titanium aluminium alloy, composite material density is better. When the amount of graphene is 0.3 wt%,self-lubricating composite material yield strength increase from 469 MPa to 555 MPa. The hardness of the self-lubricating composite was 11% higher than that of matrix, up to 468 HV; with the increase of the content of graphene composite material hardness and yield strength increases gradually, while graphene content is 0.7 wt %, reached the maximum hardness and yield strength of the composite material.